Analisis gaya bahasa puisi "hujan bulan juni" karya Sapardi Djoko Damono - Ridha Fitria Heryani; Wikanengsih Wikanengsih; Aditya Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The style of language in a poem is one of the most important elements. The right style of language used in poetry with a certain theme will make the poetic value of a poem dominant. In this study, the researcher will examine the style of language used by Sapardi Djoko Damono in his poem entitled "Hujan Bulan Juni". Although the poem can be said to be short, the language style in this poem is very dense. In this study, researchers used a qualitative descriptive method so that the results of the analysis were descriptive. The results of the analysis on the poem " Hujan Bulan Juni" found a total of 3 language styles. The first language style is Repetition, Pesonification, and Metaphor. From the results of the style analysis, it can be concluded that the atmosphere contained in the poem is an atmosphere of emotion.